Transcending beauty - Lee, Eunice Jing Ting (2016)
Transcending Beauty is a 23-minute documentary film about transgender women finding acceptance. The film delves into the stories of the organisers and several contestants of the Miss WorldMusic Tiffany 2015, a transgender beauty pageant in Singapore. This report shares the inspiration for the project, the objectives, and the journey in creating this film through the detailed pre-production, production and post-production stages.